Technical Efficiency Analysis of MSMEs Fashion Offline and Online in Surabaya - Atik purmiyati; Tamat Sarmidi; Reza Pradipta (Jurnal Ekonomi dan Studi Pembangunan, 2022)
The main purpose of this study is analyzing the level of technical efficiency of MSMEs fashion offline with offline and online in Surabaya, examine the differences between offline with offline and online, and determine the factors that affect technical efficiency. This study uses purposive sampling method with primary data. Non-parametric and parametric approach used with Data Envelopment Analysis, Independent sample T-Test and Tobit Regression. First, the results showed the average level of technical efficiency of offline MSMEs fashion was 65 percent with 8 efficient businesses. Meanwhile, the average level of technical efficiency of online and offline MSMEs fashion is 77.1 percent with 20 efficient businesses. Second, there are differences in the average efficiency of offline and online MSMEs fashion. The result of Tobit Regression on the offline MSMEs fashion show the length of business and number of store offline have positive and significant impact on technical efficiency, while number of workers and capital credit has no significant effect. While on offline and online MSMEs fashion, show the number of online stores and capital credit has a positive and significant impact on technical efficiency, while the length of business and the number of offline stores have no significant effect.